ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT GUDANG GARAM TBK - Ismail Zulhaj Tuasikal; Keiko Andromeda Ramadhania Azizah; Muhammad Sigit Nugroho; Satria Wahyu Hidayat; Tias Suningsih (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This research evaluates the financial performance of PT Gudang Garam Tbk from 2021 to 2025 using liquidity, solvency, and profitability indicators. A quantitative research design with a descriptive approach was adopted, utilizing the company's official financial statements to compute the Current Ratio (CR), Debt to Asset Ratio (DAR), and Return on Assets (ROA). The results demonstrate that liquidity is generally healthy, highlighted by a recovering Current Ratio in 2024–2025. Solvency levels are also well-managed, with the DAR remaining under the 50% threshold and tapering off by the end of the study period. However, profitability performance is less than optimal; the ROA fluctuated downwards due to cost pressures from internal operations, increased government cigarette excise rates, and fierce industry dynamics. Ultimately, the study concludes that although the firm exhibits strong financial resilience in fulfilling its obligations, optimization of operating costs is highly recommended to stimulate profit growth.